MENGEMBANGKAN KEMAMPUAN BAHASA DAN MOTIVASI BELAJAR PADA ANAK KELOMPOK A MENGGUNAKAN MODEL AKTIF - Mahriani, Ariska; Jannah, Fathul (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
The problem in this study is the low language skills and learning motivation of group A children at Mukhlisoh Barito Kuala Kindergarten. This is caused by the low language skills of children which are not yet optimal, the lack of active involvement of children in learning activities so that children's motivation to learn is low when children carry out learning activities, so that they are always not enthusiastic and do not complete their assignments. The purpose of this study was to describe teacher activities, analyze children's activities, analyze the increase in children's learning motivation, and analyze the results of children's language development. The research approach used qualitative and quantitative with the type of classroom action research (PTK) which was carried out in 4 meetings. The subjects of this study were group A children at Mukhlisoh Barito Kuala Kindergarten, totaling 26 children, including 15 boys and 11 girls. The results of this study indicate that the teacher's activity at meeting 1 obtained a score of 16 "Good" criteria increasing at each meeting until reaching a score of 20 with the"Very Good" criteria. Children's activity at meeting 1 reached 46% of the "Quite Active" criteria increasing at each meeting until at the last meeting it reached 88% of the "Very Active" criteria. The learning motivation of children in meeting 1 obtained 42% of the criteria "Less Motivated" increasing at each meeting until the last meeting reached 92% of the criteria "Very Motivated". The results of the language development of children in meeting 1 obtained 42% with the criteria "Not Developing (BB)" increasing at each meeting until the last meeting reached 88% with the criteria "Developing Very Well (BSB)". It is recommended for teachers to be used as one of the learning models to develop the quality of education, for other researchers it can be used as a reference for conducting research in expressing language. ABSTRAKPermasalahan pada penelitian adalah kurangnya kemampuan bahasa, serta motivasi belajar anak kelompok A di TK Mukhlisoh Barito Kuala. Hal ini disebabkan karena rendahnya kemampuan bahasa anak yang belum optimal, kurangnya keterlibatan anak secara aktif dalam kegiatan pembelajaran sehingga rendahnya motivasi belajar anak pada saat anak melaksanakan kegiatan pembelajaran anak, sehingga selalu tidak semangat dan tidak menyelesaikan dalam mengerjakan tugas. Objek dari penelitian ini untuk mendeskripsikan aktivitas guru, anak, menganalisis peningkatan motivasi belajar anak, dan menganalisis perkembangan bahasa anak. Pendekatan menggunakan kualitatif dan kuantitatif jenis penelitian  PTK dilaksanakan 4 siklus. Subjek penelitian  yaitu anak kelompok A TK Mukhlisoh Barito Kuala sebanyak 26 orang anak, 15 laki-laki, 11 anak perempuan. Hasil penelitian menunjukan apabila aktivitas guru pertemuan pertama mendapatkan skor 16 dengan kategori “Baik” disetiap pertemuan meningkat menjadi 20 kategori “Sangat Baik”. Aktivitas anak pertemuan pertama mecapai 46% kategori “Cukup Aktif” disetiap pertemuan meningkat pada pertemuan keempat persentase 88% kategori “Sangat Aktif”. Motivasi belajar anak pertemuan 1 memperoleh 42% kriteria “Kurang Termotivasi” disetiap pertemuan meningkat pada pertemuan ke 4 menjadi 92% kategori “Sangat Termotivasi”. Perkemangan bahasa anak pertemuan 1 memperoleh 42% dengan kriteria “Belum Berkembang (BB)” disetiap pertemuan meningkat menjadi 88% dengan kategori “Berkembang Sangat Baik (BSB)”. Disarankan bagi guru untuk dapat dijadikan salahsatu model dalam kegiatan belajar untuk menumbuhkan taraf pendidikan, untuk peneliti lain sebagai referensi dalam melaksanakan penelitian terutama pada perkembangan bahasa.